Charles D. Coxe papers - Coxe, Charles D.
Correspondence kept while serving as U. S. consul in Tunis (1806-1809) and as U.S. consul general in Tripoli (1829-1830).
U.S. consul to Tunisia and consul general to Libya.
Collection material in English, Arabic, and Italian.
Keywords: Diplomatic and consular service, American -- Libya; Diplomatic and consular service, American -- Tunisia; Tripoli (Libya); Tunis (Tunisia); Diplomats